2012
DOI: 10.1063/1.4769738
|View full text |Cite
|
Sign up to set email alerts
|

The role of secondary phase precipitation on grain boundary electrical activity in Cu2ZnSnS4 (CZTS) photovoltaic absorber layer material

Abstract: Cathodoluminescence is used to measure the recombination velocity of the heterointerfaces between Cu2ZnSnS4 (CZTS) and CuxSnySz, SnS secondary phases precipitated along the grain boundaries as well as ZnS precipitated within the CZTS grain interiors. The CZTS/CuxSnySz and CZTS/ZnS heterointerfaces had recombination velocities smaller than the bulk carrier diffusion velocity while the opposite is true for the CZTS/SnS heterointerface. Secondary phases having crystal structures compatible with CZTS (e.g., ZnS, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(64 citation statements)
references
References 30 publications
3
61
0
Order By: Relevance
“…Further evidence is obtained via room temperature panchromatic CL imaging where the precipitates are found to be highly luminescent (Fig. 3f), consistent with previous observations for ZnS in CZTS [23]. Note that the coverage of ZnS precipitates appears to be higher in the CL image compared to the backscattered image and EDX chemical maps.…”
Section: Bg Mendis Et Al Solar Energy Materials and Solar Cells 17supporting
confidence: 76%
“…Further evidence is obtained via room temperature panchromatic CL imaging where the precipitates are found to be highly luminescent (Fig. 3f), consistent with previous observations for ZnS in CZTS [23]. Note that the coverage of ZnS precipitates appears to be higher in the CL image compared to the backscattered image and EDX chemical maps.…”
Section: Bg Mendis Et Al Solar Energy Materials and Solar Cells 17supporting
confidence: 76%
“…Analysis of secondary phases and their potential impact on PV devices is reported elsewhere. 25 It should be noted that a full analysis of larger bandgap secondary phases using PL will require a shorter laser wavelength than the 458 nm Ar þ laser line used in these measurements. The PL intensity of the main CZTS feature is obtained through fitting a series of Gaussian peaks to the full PL spectra.…”
Section: Resultsmentioning
confidence: 99%
“…In general, it has been considered that the presence of secondary phases, particularly when their fundamental energy gap is larger than CZTS, will be detrimental to device performance. 14 Recent work 25 has shown that this may not be the case. The presence of secondary phases at grain boundaries in polycrystalline CZTS alters the grain boundary recombination velocity potentially increasing PV conversion efficiency.…”
Section: Introductionmentioning
confidence: 96%
“…Since current thin-film technologies mostly rely on polycrystalline materials, physical properties of extended defects, especially grain boundaries (GBs) have been investigated to understand their effects on the device efficiency [10][11][12][13][14][15][16]. Other extended defects like stacking faults (SFs) and antisite domain boundaries (ADBs) have been less documented as compared to the GBs, but since SFs in CdTe act as electron barriers and reduce the efficiency [17][18][19][20], SFs in CZTS should be investigated.…”
Section: Introductionmentioning
confidence: 99%